User perception on the use of a custom-built augmentative and alternative communication (AAC) device for elderly with Aphasia in Malaysia - Mohd Faiz Azmi; Nur Azah Hamzaid; Mas Sahidayana Mohktar; Lydia Abdul Latif (Penerbit Universiti Kebangsaan Malaysia, 2020)
Augmentative and alternative communication (AAC) device is one type of AAC which can be used to communicate besides oral speech. It has high potential to assist people with speech disabilities including elderly with aphasia (EWA) to communicate with others. This study was conducted using a newly built AAC device, TalkMate™, as a reference for AAC devices. This study aims to explore the views and perception of users regarding the use of AAC device for elderly with aphasia living in Malaysia. The EWA participants recruited for this study varied in age, severity level and experience with AAC. A qualitative design with five focus groups was conducted. The focus group discussion included caretakers, healthcare professionals and AAC device developers to gain information about multiple perspectives on AAC device use. Thematic analysis yielded four key themes: needs of using AAC, decision on using AAC, resources, and potential improvement of AAC for EWAs. This study highlighted the importance of understanding the needs of EWAs, decision, improvement on the quality of life of the EWAs, and the future of using AAC device. The main barriers of using AAC were identified to be due to funding and access to devices.